2021
DOI: 10.47162/rjme.61.4.03
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in patients with serious mental illness and possible benefits of prophylaxis with Memantine and Amantadine

Abstract: This is an open-access article distributed under the terms of a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International Public License, which permits unrestricted use, adaptation, distribution and reproduction in any medium, non-commercially, provided the new creations are licensed under identical terms as the original work and the original work is properly cited. REVIEW SARS-CoV-2 infection in patients with serious mental illness and possible benefits of prophylaxis with Memantine and Amantadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 152 publications
(160 reference statements)
2
8
0
2
Order By: Relevance
“…Moreover, our proteomic analysis of hamsters’ brains in vivo compared to human single‐cell RNA sequencing datasets corroborates the importance of the metabolic and energetic imbalance of glutamate/glutamine that may take place in the brain of neurological COVID‐19 patients. Our data bring attention not only to the physiology of the COVID‐19 brain, but also suggest that glutamate/glutamine signaling is pivotal, and may be considered either a prognostic factor or a target of specific therapies in patients that develop the neurological impairments observed during long‐covid and PASC, as memory loss and cognitive decline, and as already discussed elsewhere (Figure 7; Marinescu et al, 2020).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, our proteomic analysis of hamsters’ brains in vivo compared to human single‐cell RNA sequencing datasets corroborates the importance of the metabolic and energetic imbalance of glutamate/glutamine that may take place in the brain of neurological COVID‐19 patients. Our data bring attention not only to the physiology of the COVID‐19 brain, but also suggest that glutamate/glutamine signaling is pivotal, and may be considered either a prognostic factor or a target of specific therapies in patients that develop the neurological impairments observed during long‐covid and PASC, as memory loss and cognitive decline, and as already discussed elsewhere (Figure 7; Marinescu et al, 2020).…”
Section: Discussionsupporting
confidence: 74%
“…Clinical and animal studies have confirmed associations of decreased hippocampal volume and weight and apoptosis with depression. Hippocampal injury (hippocampal volume reduction and excessive neuronal death) is considered an important marker of the pathogenesis of depression [ 5 , 6 ]. Numerous studies have linked apoptosis to hippocampus damage.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments illustrated that memantine inhibits the SARS-CoV-2 E protein which is necessary for pathogenesis and viral proliferation (Matsunaga et al 2018 ). As well, NMDA antagonists like memantine and amantadine could be used as prophylactic agents and reduce neuropsychiatric complications in COVID-19 patients (Marinescu et al 2020 ). Memantine also reduced HCoV‐OC43 replication in the CNS, indicating that it could be utilized as an anti-viral agent and improve neurological diseases.…”
Section: Role Of Nachr Agonists/antagonists In Covid-19mentioning
confidence: 99%
“…So, memantine could be effective against the development of symptomatic COVID-19. As well, memantine can provide protection for olfactory neurocircuits, decrease the aggressiveness of NMDA receptor hyperactivity, alveolar protection, and regulate cytokine mechanisms (Marinescu et al 2020 ).…”
Section: Role Of Nachr Agonists/antagonists In Covid-19mentioning
confidence: 99%